Arsénico y medio ambiente: efectos del riego con aguas conteniendo As sobre cultivos hortícolas - Castillo, Nadia (2012)
Large areas of the Chaco Pampean plain have aquifers containing high values of As. The use of this water to irrigate horticultural species, in particular for fresh consumption, could have direct consequences on the human health as well as in the agricultural soils. The aim of this work was directed to the evaluation of the effect of the rich-arsenic water irrigation on the yield-crop of Eruca sativa. Likewise, the arsenic content in the vegetal and in the soil was analyzed. Assays with completely randomized block design and factorial arrangement (type of soil/alkalinity of water/level of As) were carried out with two type of soils of different texture (sandy loam and silty loam). The pots were kept at 90 % of field capacity, with a daily irrigation, by using waters of different alkalinity. Three concentrations of arsenic were used (100, 250 and 500 μg L- 1). Dry matter (from vegetal heated at 60 ° C) and the concentration of As in plant and in soils were the evaluated variables. The irrigation conditions affected the tenor of arsenic in plants as well as in soils, in particular in silty loam soils, according to literature. Although it is observed a trend to increase the arsenic concentration in plant through irrigation, it is not possible to establish a reliable relationship between the concentration of As in plant and performance. Moreover, the soil content increased slightly with irrigation, in particular in the silt-loam soil, without reaching hazard limits in the first sowing. While the concentration of As in fresh vegetable is below the limit established by the legislation, its use could mean a contribution to the daily intake of arsenic, which would add to the hazard caused by the drinking water with arsenic.